Pro Freeware and Open Source Solutions for Business - Whitt, Phillip. (Apress : Imprint: Apress, 2015)
Pro Freeware and Open Source Solutions for Business is a practical guide for the small business owner seeking viable alternative to expensive commercial software packages and subscriptions. This comprehensive look at the powerful alternatives to expensive proprietary software provides an illustrated overview of no-cost software solutions. In this book you will find free and open source solutions for office productivity, PDF creation, accounting, image editing and graphic design, desktop publishing, 3D design, CAD, audio and video editing, website and blog creation, customer relationship management, point of sale, networking and security, and alternatives to the Windows and Macintosh operating systems. This guide helps free the cost-conscious business owner from the bonds of expensive proprietary software by exploring the free and powerful alternatives that exist. You can save a substantial sums of money by replacing just a few commercial software titles with free and open source solutions. Learn how with Pro Freeware and Open Source Solutions for Business today.